Race and ethnicity in New York City - Krase, Jerome; Hutchison, Ray. (Amsterdam ; Boston : Elsevier, 2004)
American cities are today more diverse than at any time in history. The continuing flow of new immigrants has settled in urban and suburban areas that have undergone visible change in population and neighborhoods. While Chicago long served as the convenient and well-studied model for urban sociology, for many Los Angeles has become the focal point for study of the postmodern heteropolis. It is interesting that for sociologists New York City, especially its outer boroughs such as Brooklyn and Queens, has largely remained outside the intense gaze of urban study. As the nation's largest city New York has long had a mosaic of social worlds comparable to that of Chicago, and displays an ethnic diversity comparable to that of Los Angeles. Because New York City presents us with a less easily recognizable mosaic and a more free form scattering of ethnic social spaces, it is seldom thought of as a pre or post-modern "model" for other metropolitan areas. The eight articles presented in this volume represent both older and established ethnic and racial communities as well as new and emerging groups in New York City. These include Italian communities, African American, as well as newer Jewish, Caribbean, and Asian groups.
Includes bibliographical references.
Description based on print version record.
Keywords: Race; Ethnicity -- New York (State) -- New York; Physical anthropology & ethnography; Jewish studies; Social Science -- Sociology -- Urban; New York (N.Y.) -- Race relations